2015
DOI: 10.1073/pnas.1513433112
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy triggers HIF-1–dependent glutathione synthesis and copper chelation that induces the breast cancer stem cell phenotype

Abstract: Triple negative breast cancer (TNBC) accounts for 10-15% of all breast cancer but is responsible for a disproportionate share of morbidity and mortality because of its aggressive characteristics and lack of targeted therapies. Chemotherapy induces enrichment of breast cancer stem cells (BCSCs), which are responsible for tumor recurrence and metastasis. Here, we demonstrate that chemotherapy induces the expression of the cystine transporter xCT and the regulatory subunit of glutamate-cysteine ligase (GCLM) in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
205
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 217 publications
(221 citation statements)
references
References 57 publications
10
205
0
1
Order By: Relevance
“…We have recently demonstrated that exposure of breast cancer cells to hypoxia or chemotherapy induces the breast CSC phenotype through multiple HIF-dependent molecular pathways (18,20,54). Induction of CD47 expression provides another mechanism by which hypoxia induces the CSC phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently demonstrated that exposure of breast cancer cells to hypoxia or chemotherapy induces the breast CSC phenotype through multiple HIF-dependent molecular pathways (18,20,54). Induction of CD47 expression provides another mechanism by which hypoxia induces the CSC phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Human breast cell lines MCF10A, MCF7, HCC1954, SUM159, MDA-MB-231, and MDA-MB-435 were cultured as previously described (18,20,21,54). All cells were maintained at 37°C in a 5% CO 2 and 95% air (20% O 2 ) incubator.…”
Section: Methodsmentioning
confidence: 99%
“…depletion of BCSCs (23). High NANOG mRNA (23) or protein (41) expression in primary human breast cancers is significantly associated with increased patient mortality.…”
Section: Discussionmentioning
confidence: 99%
“…High NANOG mRNA (23) or protein (41) expression in primary human breast cancers is significantly associated with increased patient mortality. Other groups have implicated HIFs in the direct transcriptional activation of NANOG and other genes encoding pluripotency factors, both in human ESCs (42) and human cancer cells (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation